2006
DOI: 10.1002/chin.200652240
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Transportation Fuels from Biomass: Chemistry, Catalysts, and Engineering

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
1,244
0
29

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 785 publications
(1,280 citation statements)
references
References 134 publications
(269 reference statements)
7
1,244
0
29
Order By: Relevance
“…It is estimated that the worldwide production of lignocellulose amounts to 170 Â 10 9 t/year, of which 35À50 wt % is cellulose. 1 Such a tremendous, nonfood, and renewable resource is being considered as the most promising alternative to fossil resources for the sustainable production of fuels and chemicals. Since cellulose has a relatively high O/C ratio, while fuels usually possess a much lower O/C ratio, excess oxygen must be removed when cellulose is transformed into fuels, which would be achieved at the expense of C or H and thereby has a lower efficiency from the viewpoint of atom economy.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that the worldwide production of lignocellulose amounts to 170 Â 10 9 t/year, of which 35À50 wt % is cellulose. 1 Such a tremendous, nonfood, and renewable resource is being considered as the most promising alternative to fossil resources for the sustainable production of fuels and chemicals. Since cellulose has a relatively high O/C ratio, while fuels usually possess a much lower O/C ratio, excess oxygen must be removed when cellulose is transformed into fuels, which would be achieved at the expense of C or H and thereby has a lower efficiency from the viewpoint of atom economy.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 For example, propan-2-one (acetone) can be produced from an acetone-butanol-ethanol (ABE) mixture produced by the Clostridial fermentation of sugars or from the bio-oil obtained by fast pyrolysis of biomass feed stocks. 2,7 Butan-2-one can be obtained in more than 90% selectivity by aqueous-phase, acidcatalyzed dehydration of 2,3-butane diol (2, or by the decarboxylation of levulinic acid. 8−10 Finally, pentan-2-one can be produced by the ring opening hydrogenolysis of 2-methylfuran or by the monoalkylation of acetone with ethanol derived from an ABE mixture (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…14,15 We have recently shown that calcined hydrotalcite, HT, is an active and highly selective heterogeneous catalyst for the self-and crosscondensation of biomass-derived C 4 −C 11 methyl ketones to produce cyclic enones, which upon subsequent hydrodeoxygenation produce cyclic alkanes that have properties making them suitable for aviation fuel and lubricants. 6,13,16,17 Hydrotalcite-type layered double hydroxides (LDHs) are inorganic compounds with the chemical composition M 2+ 1−x M 3+ x (OH) 2 (A x/n ) n-·yH 2 O, where M 2+ and M 3+ are divalent and trivalent metal cations, x is the molar ratio of the trivalent cation [M 3+ /(M 2+ + M 3+ )] which can be varied between 17 and 33%, and A n− is an anion with charge n, most often a carbonate ion. 16 The structure of these materials is similar to that of brucite, Mg(OH) 2 , where magnesium is octahedrally surrounded by six oxygens in the form of hydroxides with the octahedral units forming infinite sheets through an edge sharing.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, the balance between Sn as a Lewis acid and TfOH as a Brønsted acid has a strong influence on product selectivity, therefore indicating that tuning of the Lewis and Brønsted acidic ratio is crucial to achieving the desired degradation of the polysaccharides and of glucose. 1 Reaction conditions: Triose (2.5 mmol), catalyst (10 mol %), methanol (4 mL), 90 °C, over 3 h. 2 Gasliquid chromatography (GLC) yield (mol %) were based on triose.…”
Section: Production Of Alkyl Levulinate From Carbohydrates Using Homomentioning
confidence: 99%
“…As such, various methods have been developed to allow the use of carbohydrates as alternative resources, and these processes could have a significant impact on reducing carbon dioxide emissions. Carbohydrates derived from both crop biomass (i.e., storage polysaccharides, such as starch) and woody biomass (i.e., cell wall polysaccharides, such as cellulose) have been considered for this purpose [1][2][3][4][5][6][7][8]. However, as the global population continues to increase, the use of limited farmland to grow crop biomass instead of food is clearly unrealistic.…”
Section: Introductionmentioning
confidence: 99%